Differential expression of toll-like receptor 6 on granulocytes and monocytes implicates the role of microorganisms in Behcet's disease etiopathogenesis - DİRESKENELİ, RAFİ HANER (SPRINGER, 2008)
The objective of this study was to investigate the expressions of toll-like receptors on neutrophils and monocytes in Behcet's disease (BD). Forty-two patients with BD were included in the study. Baseline and stimulated cells with heat shock protein-60 (HSP-60), lipopolysaccharide (LPS) and crude extract of Streptococcus sanguis (SS) were analyzed for toll-like receptor-1, -2, -4 and -6 expressions using flow cytometer. Results were confirmed using semi-quantitative PCR technique. The mean frequency of TLR-6 expressing granulocytes in BD patients was significantly lower than in controls (4.2 +/- 0.6 vs. 9.2 +/- 0.6 and 8.0 +/- 1.4, BD vs. rheumatoid arthritis (RA) and healthy control (HC); P < 0.05). TLR-6 expressing granulocyte population was enhanced after stimulation with HSP-60 and SS (20 +/- 0.5 and 12.8 +/- 0.6, respectively). Decreased TLR-2 expression was noted in monocytes of BD patients after stimulation with HSP-60 and LPS (71.0 +/- 0.5 and 73.0 +/- 0.5; P < 0.02, for both antigens). Functional abnormalities of these receptors or different activation cascades by different microorganisms are associated with disease pathogenesis in Behcet's disease.
Keywords: Behcet's disease; innate immunity cells; toll-like receptors; HEAT-SHOCK-PROTEIN; RHEUMATOID-ARTHRITIS; DISCRIMINATION; STREPTOCOCCUS; LIPOPEPTIDE; RECEPTOR-6; CELLS